ESG Disclosure, Cost of Debt, and the Moderating Role of Board Characteristics - Vicky Putra Surifran; Se Tin Se Tin; Lidya Agustina (Universitas Kristen Maranatha, 2026)
Purpose – This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on the cost of debt and to investigate the moderating role of board of commissioners characteristics in non-financial firms in Indonesia. Design/Methodology/Approach – This study employs a quantitative approach using Ordinary Least Squares (OLS) regression and Moderated Regression Analysis (MRA). The data are collected from annual reports, financial statements, and the Refinitiv database of non-financial firms listed on the Indonesia Stock Exchange during the period 2020–2024, resulting in 205 observations. Findings – The results indicate that ESG disclosure has a positive and significant effect on the cost of debt. Furthermore, the proportion of independent commissioners negatively and significantly moderates the relationship, while board size shows a positive and marginally significant moderating effect. In contrast, female representation does not exhibit a significant moderating role. Research limitations/Implications – The findings suggest that the relationship between ESG disclosure and the cost of debt is highly contextual and depends on the effectiveness of corporate governance mechanisms. Practically, the cost of debt is determined by creditors’ risk perceptions, highlighting the importance of credible governance structures in supporting ESG disclosure. Keywords: Board Characteristics, Cost of Debt, Corporate Governance, ESG Disclosure